Implementación de ferias gastronómicas promoviendo la buena nutrición que ayude en el desempeño intelectual de los niños y niñas de 5 a 6 años de edad, de la escuela general de educación básica “Pujili”, del cantón Pujilí, provincia de Cotopaxi en el año lectivo 2012 – 2013 - Calderón Togra, María Del Carmen (2015)
This research work was made to upgrade children nutritional level from 5 to 6 years old in Pujilí school, located in Pujilí town, Cotopaxi province during the school year 2012-2013 period. Through developing research we can note the importance at healthy and nutritive food applying correct hygiene, manipulation and preparation. The family infants are the example, at lunch time they need to teach what kind of food to consume. The objective focuses on the realization of food fairs to promote a good nutrition of the children’s from 5 to 6 years old and their intellectual development, showing and the benefits of this diet. Focus was the combination….